2010
DOI: 10.1055/s-0030-1258082
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of Novel Pyrrolidine Dendrimers by Terminal Group Modification through 1,3-Dipolar Cycloaddition Reaction

Abstract: A series of novel dendrimers with pyrrolidine as surface group has been achieved in high yields by terminal-group modification on chalcone dendrimers through the application of 1,3-dipolar cycloaddition reaction. In 1,3-dipolar cycloaddition, azomethine ylides (AMY) with alkenes afforded five-membered N-methyl pyrrolidine. The formation of N-methyl pyrrolidine in the dendritic structure would be an important candidate in the field of biology and pharmacology.Design and synthesis of dendritic architectures have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Pyrrolidine. Rajakumar et al 85 reported the synthesis of some novel star-shaped molecules with pyrrolidine side arms 78, 80, 82 and 84 in high yields through 1,3-dipolar 86 reported the synthesis of multi-armed thiazole derivatives 88a and 88b in 67 and 69% yields, respectively, by the reaction of tris(aldehyde thiosemicarbazones) 85a and 85b with each of 2-bromo-1-phenyl ethanone 86 and 2-bromo-1-(4chlorophenyl)ethanone 87 in ethanol at reux in the presence of TEA (Scheme 22). The same methodology was extended to the preparation of tetrakis-and hexakis(thiazoles) 90a, 90b, 92a and 92b in good yields from the corresponding poly(aldehyde thiosemicarbazones) 89a, 89b, 91a and 91b (Schemes 23 and 24).…”
Section: Ssms With Alicyclic Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrrolidine. Rajakumar et al 85 reported the synthesis of some novel star-shaped molecules with pyrrolidine side arms 78, 80, 82 and 84 in high yields through 1,3-dipolar 86 reported the synthesis of multi-armed thiazole derivatives 88a and 88b in 67 and 69% yields, respectively, by the reaction of tris(aldehyde thiosemicarbazones) 85a and 85b with each of 2-bromo-1-phenyl ethanone 86 and 2-bromo-1-(4chlorophenyl)ethanone 87 in ethanol at reux in the presence of TEA (Scheme 22). The same methodology was extended to the preparation of tetrakis-and hexakis(thiazoles) 90a, 90b, 92a and 92b in good yields from the corresponding poly(aldehyde thiosemicarbazones) 89a, 89b, 91a and 91b (Schemes 23 and 24).…”
Section: Ssms With Alicyclic Coresmentioning
confidence: 99%
“…These observations clearly demonstrate that perturbation of molecular structure has remarkable inuence on their bulk macroscopic properties. 85 4.3.1.1.3.3. 1,3,4-Thiadiazole.…”
Section: Ssms With Alicyclic Coresmentioning
confidence: 99%
“…Therefore, the 1,3-dipolar cycloaddition reaction of ninhydrin, L-proline and chalcones provided spiroindane-1,3-dione pyrrolizidines in good yields and with high regio-and stereoselectivity (Scheme 4) [64]. Chalcone dendrimers undergo 1,3-dipolar cycloaddition reaction with sarcosine and an excess of paraformaldehyde in refluxing toluene to prepare Nmethylpyrrolidine dendrimers [65]. Moemeni et al used a one-pot four-component 1,3-dipolar cycloaddition reaction of ninhydrin, arylenediamines, sarcosine and chalcones to prepare highly substituted pyrrolidines in good yields and stereoselectivity (Scheme 5) [66].…”
Section: -85%mentioning
confidence: 99%
“…Recently, we have reported the synthesis of dendrimer with dimethyl isophthalate, 14 pyrrolidine, 15 quinoline, 16 and pyreno-chalcone 17 as surface groups with 1,2,3-triazole as…”
Section: Dendrimersmentioning
confidence: 99%